Cortical strut allografting in reconstructive orthopaedic surgery - Judas, F (2011)
Many approaches are used in the repair of skeletal defects in reconstructive orthopaedic surgery, and bone grafting is involved in virtually every procedure. Autografting remains the gold standard for replacing bone loss. However, the limited amount of bone that can be harvested and the morbidity associated with that procedure are major constraints to the clinical use of autografts. In contrast, bone allografts can be used in any kind of surgery, whether involving minor defects or major bone loss. Cortical strut allografts unite to host bone through callus formation, restoring bone stock and can be used as an onlay biological plate. These struts can be made from hemicylinders of tibia being fixed to host bone by circumferential metallic cables or by screws. The purpose of this study was to analyze the radiographic outcomes of twelve cryopreserved cortical onlay strut allografts, used in a group of nine patients, for revision hip arthroplasty of the femoral side, to stabilize femoral periprosthetic fractures, to reinforce poor cortical bone and to treat one atrophic femoral nonunion. The average follow-up period was 4.3 years (range, 1.6 to 9 years). No fractures, nonunions or progressive resorption of the bone allografts were observed. All struts were incorporated to the native femur with minimal resorption, within the first year after surgery. There was no failure of any of the allograft reconstructions.The results obtained show that cortical onlay strut allografts, either alone or in conjunction with metallic plate or cancellous bone allografts, are a valuable adjunct for reconstructive surgery of the hip and to treat atrophic femoral nonunion.